Chronic Cold Stress Alters the Skin Mucus Interactome in a Temperate Fish Model - Sanahuja, Ignasi; Fernández-Alacid, Laura; Sánchez-Nuño, Sergio; Ordóñez-Grande, Borja; Ibarz, Antoni (Frontiers in Physiology, 2019)
Temperate fish are particularly sensitive to low temperatures, especially in the northern Mediterranean area, where the cold season decreases fish-farm production and affects fish health. Recent studies have suggested that the skin mucus participates in overall fish defence and welfare, and therefore propose it as a target for non-invasive studies of fish status. Here, we determine the mucus interactome of differentially expressed proteins in a temperate fish model, gilthead sea bream (Sparus aurata), after chronic exposure to low temperatures (seven weeks at 14ºC). The differentially expressed proteins were obtained by 2D-PAGE of mucus soluble proteins and further assessed by STRING analyses of the functional interactome based on protein-protein interactions. Complementarily, we determined mucus metabolites, glucose and protein, as well as enzymes involved in innate defence mechanisms such as total protease and esterase. The cold mucus interactome revealed the presence of several subsets of proteins corresponding to Gene Ontology groups. “Response to stress” formed the central core of the cold interactome, with up-regulation of proteins such as heat shock proteins (HSPs) and transferrin; and down-regulation of proteins with metabolic activity. In accordance with the low temperatures, all proteins clustered in the “Single-organism metabolic process” group were down-regulated in response to cold, evidencing depressed skin metabolism. An interactome subset of “Interspecies interaction between species” grouped together several up-regulated mucus proteins that participate in bacterial adhesion, colonization and entry, such as HSP70, lectin-2, ribosomal proteins, and cytokeratin-8, septin and plakins. Furthermore, cold mucus showed lower levels of soluble glucose and no adaptation response in total protease or esterase activity. Using zymography, we detected the up-regulation of metalloprotease-like activity, together with a number of fragments or cleaved keratin forms which may present antimicrobial activity. All these results evidence a partial loss of mucus functionality under chronic exposure to low temperatures which would affect fish welfare during the natural cold season under farm conditions.